THE DEVELOPMENT OF UNIVERSITY-BASED ACTUARIAL EDUCATION IN CANADA - Fursenko, Tetiana (Studies in Comparative Education, 2017)
The paper is aimed at figuring out the current state of actuarial education provided by Canadian universities tracing the peculiarities of its development and concentrating mainly on the process of the University accreditation program implementation. The academic novelty of the article lies in the fact that in national comparative pedagogy it is the first attempt to analyze Canada`s university-based actuarial education. Having studied the documents, we may conclude that the UAP is a set of the criteria and requirements having fulfilled which a university is granted the right to provide its actuarial students with the opportunity of exemption from the professional exams set by the SOA and the CAS on their way to the ACIA or FCIA designations. It is worth mentioning that in many ways Canada is the first country in North America which is now actively trying to bring the profession of an actuary into academic environment. The reasons for implementing such measures are obvious: university settings open wide prospects for research activities as well as provide more predictable route for becoming a qualified actuary as compared to its alternative of going through the set of the exams established by the above mentioned bodies. By integration of formal and informal actuarial education into a single whole it is possible to strengthen the profession. However, the main obstacle on the way to success of the UAP is the assumption that by shifting educational process to universities we are reducing professional standards. Under such circumstances the UAP policy is characterized by stringent selection criteria as for the syllabi, course outlines, faculty members, minimum exemption grades etc.. The main of them can be broadly summarized as follows. In order to be accredited a university has to provide 85 % coverage of the syllabus of the professional bodies, to have at least 4 full-time faculties, one of them has to be a fellow of the CIA, rigid testing and examination procedures are a must; for students to get the exemption, the grade on each of the courses in question has to be not lower than «B» or higher. In order to figure out whether a university satisfies the standards, lots of administrative bodies have been created or engaged: the Eligibility and Education Council, the CIA, the Accreditation committee, accreditation panels, appeal investigation panels etc. For the time being, there are 11 universities which comply with the given requirements. Overall, the UAP can be considered as a successfully implemented experiment.